PHYSIOTHERAPY AND ITS CHALLENGE AGAINST COVID-19: PHYSIOTHERAPY AND COVID-19 - Pereira Rodriguez, Javier Eliecer (2020)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of a rapidly spreading illness. The coronavirus disease 2019 (COVID-19), affecting thousands of people around the world; currently, more than 300,000 cases are reported worldwide due to COVID-19 and statistics mention that 5% of the population infected by COVID-19 requires intensive care units with mechanical ventilation support. It ́s for that urgent guidance for clinicians, physiotherapist and nurse caring for the sickest of these patients is needed. Highlighting that this document focuses mainly on professionals who practice physical therapy.